Evidence of Fire Use by Homo erectus pekinensis: An XRD Study of Archaeological Bones From Zhoukoudian Locality 1, China - Huang, Chao; Li, Jingshu; Gao, Xing (Frontiers in Earth Science, 2022)
Zhoukoudian Locality 1 is well known both for the discovery of Homo erectus fossils and for the presence of early evidence of controlled use of fire by hominins; However, the nature of the latter had been seriously questioned since mid-1980s. To obtain substantial evidences of fire use by hominins, we combine macroscopic observations and XRD analysis on 23 fossil bones from new excavations in Layers 4 and 5. The crystalline index shows that at least 15 fossil bones were heated above 600 ℃, and this is partly consistent with macroscopic observations. The high intensity burning of bones may indicate strong evidence of hominin-controlled use of fire at Layer 4. Future work should focus on archaeological materials from lower layers to improve our understanding of the nature of colored bones and gain more solid evidence of fire use by early humans at Zhoukoudian.